2010
DOI: 10.1016/j.jchromb.2010.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of OH° radical/pressure dependence of arginase activity using a molecular chromatography approach

Abstract: Arginase is an enzyme which plays a role in pathophysiology such as hypertension. Here we demonstrated for the first time the direct implication of pressure and OH° radical formation on the arginase activity via a novel analytical procedure. Pressure increased arginase activity in the range 12-52bars. Activation by OH° radical showed a hyperbolic response. The OH° radicals produced were significantly inhibited by sulfasalazine (SAZ) and the inhibition of OH° radicals parallels the inhibition of arginase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The catalysis rate and the V max values were higher at the presence of CNPs in the medium ( Figure 3 and Table 1), while a little decrease was observed on the K m . These data indicated classical activation kinetic with an increase in the substrate affinity to the active site [14][15][16] and suggested that CNPs affect positively proximity and enzyme orientation for its interaction with the substrate. This can be achieved by a structural orientation of histidine residue in the active site gorge, by increasing affinity of substrate to the peripheral site or by increasing the rate of substrate entering to the active site following a structural conformational change.…”
Section: Kinetic Studymentioning
confidence: 67%
“…The catalysis rate and the V max values were higher at the presence of CNPs in the medium ( Figure 3 and Table 1), while a little decrease was observed on the K m . These data indicated classical activation kinetic with an increase in the substrate affinity to the active site [14][15][16] and suggested that CNPs affect positively proximity and enzyme orientation for its interaction with the substrate. This can be achieved by a structural orientation of histidine residue in the active site gorge, by increasing affinity of substrate to the peripheral site or by increasing the rate of substrate entering to the active site following a structural conformational change.…”
Section: Kinetic Studymentioning
confidence: 67%